Compliance With Safety and Self-Isolation Among Nursing Students Living in Dormitories During Pandemic - Lase, Margaret; Bate’e, Nisra; Waruwu, John; Watania, Lani Natalia; Fangidae, Erniyati (Department of Nursing, Faculty of Health Sciencce, Universitas Brawijaya, 2023)
Compliance is an attitude or behaviour as an effort to carry out requests or orders from others. Self-isolation also applies to students living in Western Indonesian Private University dormitories. It is intended for people with symptoms of COVID-19, such as coughing, shortness of breath, fever, sore throat, runny nose, other respiratory diseases, and a history of contact with suspected patients. Research This study aims to identify a description of nursing students' compliance in independent isolation in a dormitory at a private university in Western Indonesia. This study uses a retrospective type of research that takes data from March to September 2021 using quantitative research methods and a descriptive approach with sampling using the Purposive Sampling technique. The population in this study were final-year students with a sample size of 88 respondents. The measuring instrument in this study is a questionnaire with 11 questions. This questionnaire was tested for validity and reliability by 30 respondents who were final-year students. Researchers used univariate data analysis to describe student compliance in self-isolation. The results show that the level of compliance of the respondents was 59.1%, and non-compliance was 40.9%. In conclusion, most of the students were obedient in carrying out self-isolation. However, implementing health protocols should be maintained as preventive action for COVID-19.